BEHAVIOR PROBLEM IMPACT TO DECREASING KIDNEY FUNCTION AMONG MIGRANT WORKERS - isroin, laily; Suandika, Made (Kesmas, 2019)
Indonesian Workers were undergoing 18% of hemodyalysis from the number of hemodyalysis patients. They did not know about CRF. The study aimed to analyze the behavior of migrant workers who were suffering hemodyalysis. The study used a qualitative design with a phenomenological approach, that is carried out on former migrant workers who suffer from chronic kidney failure. Indepth interview used as data collection. While data validation used triangulation and confirmability. Data analysis techniques was done by reducing and interpreting the data. The study show migrant workers behavior before becoming migrant workers were very pathetic. They often drunk kind of energy drinks. Further, following the lifestyles of migrant countries such as drinking alcohol, soft drinks, fast food becoming their routine activities as lack of drinking water, vegetables, fruit, and also rarely did exercises. Migran workers activities influenced by the work system and individual interests to get excess income, then they chose to work overtime as their priority. In conclusion, the problem of migrant workers' behavior and hypertensive hereditary disease has an impact on decreasing kidney function. Migrant workers have no knowledge of healthy lifestyles and CRF. Wrong perceptions and attitudes of migrant workers to support culture in migrant countries.